Examining Employees’ Perception In The Postal Department: A Comprehensive Review - Kaur, Amandeep; Aggarwal, Parmod Kumar (Gyan Management Journal, 2024)
The postal department of India fosters national integration and socio economic development by acting as a cornerstone of communication,  connectivity and commerce. With the changing business scenario, practices  of business organization have changed dramatically which ultimately  redefines the role of employees. This review study examines employees’  perceptions within the postal department, aiming to understand the various  factors that influence their perception. Through a comprehensive analysis of  existing literature, including empirical studies and theoretical frameworks,  the research highlights key determinants such as job satisfaction, workplace  culture, reward system, management citizenship, communication,  and opportunities for growth. By synthesizing these findings, the study  underscores the importance of addressing these factors to enhance employee  satisfaction, foster a positive work environment, and ultimately improve  organizational performance within the postal sector. This abstract provides  valuable insights for postal department managers and policymakers seeking  to optimize employee perceptions and improve overall effectiveness in the  workplace.
Keywords: Employees; perception; Engagement; Job satisfaction and Motivation